Breast cancer drugs: FDA approval, development time, efficacy, clinical benefits, innovation, trials, endpoints, quality of life, value, and price - Michaeli, Julia; Michaeli, Christoph T.; Trapani, Dario; Albers, Sebastian; Dannehl, Dominik; Würstlein, Rachel; Michaeli, Daniel (Breast cancer, 2024)
Objective This study analyzes the development, benefits, trial evidence, and price of new breast cancer drugs with US Food and Drug Administration (FDA) approval. Methods We identified 26 drugs with 42 FDA-approved indications for early and metastatic breast cancer (2000-2023). Data were collected from FDA labels, clinicaltrials.gov, and Medicare and Medicaid. Overall survival (OS) and progression-free survival (PFS) hazard ratios (HRs) and tumor response’s relative risk (RR) alongside objective response rate (ORR) were meta-analyzed. Results The median development time for breast cancer drugs was 7.8 years (95% CI 6.2-10.8). 26% of treatments were considered innovative (“first-in-indication”) with 88% acting via a targeted mechanism. 64% were small molecules, 19% antibodies, and 18% antibody-drug conjugates. 38% were approved for HR + and 31% for HER2 + breast cancer. 6 indications were for early and 36 for metastatic breast cancer. Indications utilized FDA’s special programs: orphan (2%), fast track (24%), accelerated approval (19%), priority review (74%), breakthrough therapy (44%). Approval was predominantly supported by phase 3 trials (88%) of randomized controlled design (66%), enrolling a median of 585 patients (IQR 417-752) at 181 centers (IQR 142-223) across 19 countries (IQR 17-20). New drugs’ HR were 0.78 for OS (95% CI 0.74-0.82) and 0.59 for PFS (95% CI 0.54-0.64) with a RR for tumor response of 1.61 (95% CI 1.46-1.76). Median improvements of OS were 2.8 months (IQR 1.8-5.8) and PFS were 4.4 months (IQR 2.2-7.1). In single-arm trials, the average ORR was 31% (95% CI 10-53). In meta-regressions, the correlation between OS/PFS was 0.34 (p = 0.031) and OS/response was 0.01 (p = 0.435). 60% of treatments had a ‘high-value’ ESMO-MCBS score with 14% demonstrating improvements in quality of life. The median price was $16,013 per month (95% CI 13,097-17,617). There was no association between prices and patient benefit. The median value per life year gained was $62,419 (IQR 25,840-86,062). Conclusions Over the past two decades, the development of innovative and effective drugs transformed the treatment landscape for breast cancer patients. Yet, investigators and regulators must safeguard that highly-priced new drugs demonstrate improvements in patient-centered clinical endpoints: overall survival and quality of life.
Online veröffentlicht: 25. September 2024
Gesehen am 21.01.2025